A cell type annotation Jamboree—Revival of а communal science forum. Issue 9 (25th June 2020) - Peshkin, Leonid; Kirschner, Marc W.
Summary: Cell Atlases are currently being constructed for human tissues as well as several model organisms. New technologies make creation of vast datasets in many species possible, but the value of such data crucially depends on the quality of annotation. The tools of annotating single cell data and creating knowledge representations comparable across organisms have been lagging. We argue that successfully creating Cell Atlases will require a revival of a boot‐camp style forum for communal annotation combined with an intensive learning workshop, dubbed a "Jamboree". We report on our experience of successfully developing a structure and curriculum and running such a Jamboree for Xenopus Embryonic Cell Types at the Janelia Farms campus of the Howard Hughes Medical Institute.